Comparison of vascular‐related diseases in their associations with carotid femoral pulse wave velocity: From the Beijing Vascular Disease Patients Evaluation Study (BEST Study). Issue 11 (19th August 2019) - Liu, Huan; Xie, Wuxiang; Liu, Jinbo; Zhao, Hongwei; Wu, Yangfeng; Wang, Hongyu
Summary: Aims: Carotid femoral pulse wave velocity (CF‐PWV) is associated with vascular‐related diseases. However, this association has rarely been compared in the same study population, which would improve our understanding of the role of these diseases in developing arteriosclerosis. This study was designed to assess arterial function in different vascular‐related diseases and the potential interrelationships between these diseases and arteriosclerosis. Methods: There were 13 798 participants with or without established vascular‐related diseases, including hypertension, diabetes, coronary artery disease (CAD), stroke and peripheral artery disease (PAD), enrolled into the study from 2010 to 2016, comprising 6648 males and 7150 females. The odds ratio (OR) of arteriosclerosis (defined as CF‐PWV >12 m/s) in associations with the vascular‐related diseases was modelled using multivariable logistic regression analyses to adjust for possible confounders. Results: Compared with participants without vascular‐related diseases, those presenting the diseases showed a significantly higher prevalence and age‐ and sex‐adjusted OR of arteriosclerosis (all P  < .001). After further adjustment for hypertension, the ORs became much smaller and not significant for CAD or stroke. Compared with apparently healthy participants, participants with each of the diseases showed a significantly higher adjusted OR (range: 2.46‐3.30, all P  < .001); participants with each vascular‐related disease only showed much smaller and non‐significant ORs, except for hypertension (OR = 2.73, 95% CI: 2.46, 3.04). After further adjustment for hypertension, these ORs became non‐significant (range: 0.81‐1.36, all P  > .05). Conclusions and clinical implications: The associations between arteriosclerosis and diseases other than hypertension were largely explained by the association with hypertension, indicating that hypertension could be the single most important factor that leads to arteriosclerosis. Trial registration: ClinicalTrials.gov NCT02569268.